Analysis of The Legal Reasoning in Judgment No. 454/PID.B/2024/PN.SBY regarding Crimes against Life - Jasmine Fahira Maulana; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyse the judge's ruling (Ratio Decidendi). The analysis begins with suspicions that seek the truth through in-depth examination of the case. The judge's decision to acquit the defendant of all charges brought by the public prosecutor-under Articles 338 and 351-raises the researcher's curiosity. The judge concluded that the defendant's actions did not constitute a criminal offense. However, the actions meet the criteria of assault under Article 351 of the Indonesian Penal Code. Assault is an intentional act against a person's body that causes pain or injury and may even result in death. This research uses a normative legal method by analysing a case using a statutory approach. Data were obtained from secondary sources through literature, including primary and secondary legal materials, then analyzed qualitatively and concluded deductively. The findings show that the panel of judges issued a verdict acquitting the defendant of all charges in an assault case resulting in death (Judgment No. 454/Pid.B/2024/PN.Sby), which the researcher considers far from achieving justice. In the researcher's view, this ruling is incorrect because the defendant committed a clear criminal act without sufficient justification to negate the offense. The judge's legal considerations in ruling No. 454/Pid.B/2024/PN.Sby show that the defendant met the elements of a criminal offense under Article 351 paragraph (3) in conjunction with Article 55 of the Criminal Code, and the evidentiary requirements outlined in Article 183 of the Criminal Procedure Code were fulfilled.